Pemikiran politik Sayyid Jamal al-Din al-Afghani mengenai konsep pembinaan peradaban ummah & respons masyarakat terhadapnya - Azman Md Zain,; Mahyuddin Abu Bakar, (Universiti Kebangsaan Malaysia, 2007)
Sayyid Jamal al-Din al-Afghani was the founder of reformist movement in the Muslim modern world. His political idea was to stir the Muslims from their nightmare of being colonized by Westerns. Al-Afghani urged the Muslims to fight against western colonialisation in their country. This article discusses and elaborates on how rulers, scholars and westerners responded to al-Afghani’s thinking